Mechanical Behavior of Osteoporotic Bone at Sub-Lamellar Length Scales - Jimenez-Palomar, Ines; Shipov, Anna; Shahar, Ron; Barber, Asa H. (Frontiers in Materials, 2015)
Osteoporosis is a disease known to promote bone fragility but the effect on the mechanical properties of bone material, which is independent of geometric effects, is particularly unclear. To address this problem, micro-beams of osteoporotic bone were prepared using focused ion beam (FIB) microscopy and mechanically tested in compression using an atomic force microscope (AFM) while observing using in situ electron microscopy. This experimental approach was shown to be effective at measuring the subtle changes in the mechanical properties of bone material required to evaluate the effects of osteoporosis. Osteoporotic bone material was found to have lower elastic modulus and increased strain to failure when compared to healthy bone material, while the strength of osteoporotic and healthy bone was similar. A mechanism is suggested based on these results and previous literature that indicates degradation of the organic material in osteoporosis bone is responsible for resultant mechanical properties.